![3 \sqrt{3}](https://tex.z-dn.net/?f=3%20%5Csqrt%7B3%7D%20)
please mark me as brainlist
Answer:
,
,
,
,
, ![2\frac{3}{4}](https://tex.z-dn.net/?f=2%5Cfrac%7B3%7D%7B4%7D)
Step-by-step explanation:
,
,
,
,
, ![\frac{5}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D)
Order everything, negative to the left side and positive to the right side
<u><em>Negative numbers:</em></u>
,
, ![-\frac{3}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B4%7D)
<u><em>Positive numbers:</em></u>
,
, ![\frac{5}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D)
<em><u>Now order it on a number line:</u></em>
,
,
,
,
, ![2\frac{3}{4}](https://tex.z-dn.net/?f=2%5Cfrac%7B3%7D%7B4%7D)
Let's solve this system of equations through substitution.
We have these two equations.
-7x-2y=14
6x+6y=18
Now let divide the second equation by 6.
6x+6y=18 ----> x+y=3
Next, let us move y to the right side of the equation.
x+y=3 -------> x=3-y (x equals 3-y)
Because we found out that what x is in terms of y, we can input that in for every instance of x in this equation below.
-7x-2y=14 becomes -7(3-y)-2y=14 (Why? Because x equals 3-y!)
We have a one variable equation now and can solve for y.
-7(3-y)-2y=14
-21+7y-2y=14
5y=35
y=7
Plug in 7 for y in any equation to find x.
x+y=3
x+7=3
x=-4
answer: x=-4, y=7
I don’t see a picture or anything? Can you explain more I don’t know the sides
Answer:
15,700
Step-by-step explanation:
The formula is 3.14(r^2)h
Hope this helped :)